Ladies who launch : embracing entrepreneurship & creativity as a lifestyle - Colligan, Victoria (Tantor Media, 2009)
Ladies Who Launch is the first company to define the feminine approach to launching a business and to make the connection between starting a business and bringing creativity into your life with self-esteem and happiness. The four-step incubator process gives women the courage to follow a cherished but unfulfilled dream, providing a proven approach to catapulting a lifestyle, relationship, or occupation to an infinitely higher level.